The impact of WhatsApp on first-year students' transition to university life - Qiqieh, Sura; Hussein, Elham; Abou Adel, Mohammed (Frontiers in Education, 2025)
In a world that is rapidly becoming more digitized, it is likely for first-year students who come from diverse socio-economic and cultural backgrounds to face a number of challenges during their academic and social adaptation to university life. In this study, we explore the influence of the use of WhatsApp on the transition experiences of 205 first-year students attending Al Ain University in the United Arab Emirates. More specifically, the study explores the correlation between first-year students' usage of WhatsApp and their academic and social adaptation. Areas related to the academic aspect include group discussions and academic support, while social aspects include social experiences and level of adaptation to the social context. A structured questionnaire with predefined response options was constructed and then distributed among first-year students enrolled in various colleges. Descriptive, inferential statistics, and correlation techniques were used to analyze data and address research inquiries. The results revealed that WhatsApp is a pivotal tool for first-year university students with a strong inclination toward academic collaboration and support. Furthermore, WhatsApp has a notable influence on academic life, assisting in receiving university announcements, seeking advice from professors, and adapting to university responsibilities. Additionally, WhatsApp significantly contributes to students' social experience, aiding connections with fellow students and organizing social events.